Is Distributional Justice Equivalent to Prosocial Sharing in Children’s Cognition? - Zhu, Yuning; Zhang, Jingmiao; Liu, Xiuli (Frontiers in Psychology, 2022)
Distribution and sharing are social preference behaviors supported and shaped by selection pressures, which express individuals’ concern for the welfare of others. Distributive behavior results in distributive justice, which is at the core of moral justice. Sharing is a feature of the prosocial realm. The connotations of distribution and sharing are different, so the principles, research paradigms, and social functions of the two are also different. Three potential causes of confusion between the two in the current research on distribution and sharing are discussed. First, they share common factors in terms of individual cognition, situation, and social factors. Second, although they are conceptually different, prosocial sharing and distribution fairness sensitivity are mutually predictive in individual infants. Similarly, neural differences in preschoolers’ perception of distribution fairness predict their subsequent sharing generosity. Finally, similar activation regions are relevant to distribution and sharing situations that need behavioral control on a neural basis.